2016
DOI: 10.1002/ffj.3360
|View full text |Cite
|
Sign up to set email alerts
|

Effects of xanthan and sugar on the release of aroma compounds in model solution

Abstract: The effects of the interaction of xanthan and sugar on the release of aroma compounds (α‐pinene, ethyl acetate, ethyl butyrate, perillaldehyde, hexenal, and d‐limonene) were investigated in model solutions (xanthan, sugar and xanthan‐sugar solutions). The released aroma compounds were analysed by solid‐phase microextraction and gas chromatography‐mass spectrometer (SPME/GC‐MS). The results showed that the six aroma compounds decreased differently in the 0.4 g·L‐1 xanthan solution. A slightly stronger release o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…1,3 Maltodextrins are classified on the basis of their dextroseequivalent (DE) values and the source of starch from which they originated. [7][8][9][10][11][12][13][14][15][16][17][18] These researches reported that the release of volatile compounds in food systems can be affected by van der Waals forces, hydrogen bonds, and hydrophobic interactions between volatile compounds and polysaccharide matrices. 4,5 In general, the properties of maltodextrins with lower DE values (ie, less hydrolyzed) are more close to those of starch, from which they originate; that is, their hygroscopicity and solubility increase whereas their crystallinity and bulking capacity decrease as the DE value increases.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…1,3 Maltodextrins are classified on the basis of their dextroseequivalent (DE) values and the source of starch from which they originated. [7][8][9][10][11][12][13][14][15][16][17][18] These researches reported that the release of volatile compounds in food systems can be affected by van der Waals forces, hydrogen bonds, and hydrophobic interactions between volatile compounds and polysaccharide matrices. 4,5 In general, the properties of maltodextrins with lower DE values (ie, less hydrolyzed) are more close to those of starch, from which they originate; that is, their hygroscopicity and solubility increase whereas their crystallinity and bulking capacity decrease as the DE value increases.…”
Section: Introductionmentioning
confidence: 99%
“…The DE value is the degree of hydrolysis of starch into glucose syrup: the terms "maltodextrin" and "corn syrup solids" are generally used for DE values of <20 and ≥20, respectively. [7][8][9][10][11][12][13][14][15][16][17][18] Karaiskou et al 8 studied the release of limonene and trans-2-hexenal from gum arabic or egg yolk/xanthanstabilized oil-in-water emulsions. 6 Many studies have investigated the diverse effects of polysaccharides on the release and retention of flavor compounds.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations